Development of four PCR-based methods to differentiate tilefish species (Branchiostegus japonicus and B. albus). (15th January 2019) - Kang, Tae Sun
Highlights: Sensitive Branchiostegus japonicus -specific and tilefish primer sets were designed. Accurate four PCR-based methods were developed for B. japonicus identification. Ultra-fast qPCR completed entire analysis within 30 min for on-site identification. The labeling compliance of 47 commercial red tilefish products was verified. Abstract: The red tilefish ( Branchiostegus japonicus ) is an important ingredient and fishery resource in South Korea. Branchiostegus japonicus -specific and tilefish primer sets were designed, and four PCR-based methods were developed to differentiate B. japonicus and B. albus species. The specificity of the conventional and quantitative real-time PCR (qPCR) developed was confirmed using twenty species, showing no cross-activity, and the limit of detection was 0.1–0.001 ng/µL. Their accuracy was validated using a forensically informative nucleotide sequencing method on forty-seven red tilefish products. These two methods were further improved to develop direct triplex PCR and ultra-fast qPCR for the on-site food analysis, which could complete the entire analytical procedure within either 90 or 30 min, while maintaining the same accuracy. Therefore, these four PCR methods can be efficiently customized in various analytical areas and conditions, including field analysis, rapid screening, quality control, and labeling compliance, required by food manufacturing industry and regulatory authorities.